University leadership practices among Muslim women academic leaders of two selected public universities in Malaysia and Saudi Arabia - Al Maki, Samah Hatem (2017)
Muslim women have achieved many significant milestones professionally in higher education. It is no longer unusual to see Muslim women climb the leadership ladder and contribute for positive development in higher education. This study was conducted to explore university leadership practices among Muslim women academic leaders two public University in Malaysia and Saudi Arabia. Specifically, this study focused on: Firstly, What does leadership mean to Muslim Women academic Leaders. Secondly, how do Muslim women academic leaders practice leadership in higher education. Thirdly, what are the challenges that Muslim women leaders face in higher education and how do Muslim women leaders cope with challenges in leadership?